The potential of repurposing clemastine to promote remyelination - Yamazaki, Reiji; Ohno, Nobuhiko (Frontiers in Cellular Neuroscience, 2025)
White matter in the central nervous system comprises bundled nerve fibers myelinated by oligodendrocytes. White matter injury, characterized by the loss of oligodendrocytes and myelin, is common after ischemic brain injury, inflammatory demyelinating diseases including multiple sclerosis, and traumatic damage such as spinal cord injury. Currently, no therapies have been confirmed to promote remyelination in these diseases. Over the past decade, various reports have suggested that the anti-muscarinic drug clemastine can stimulate remyelination by oligodendrocytes. Consequently, the repurposing of clemastine as a potential treatment for a variety of neurological disorders has gained significant attention. The therapeutic effects of clemastine have been demonstrated in various animal models, and its mechanisms of action in various neurological disorders are currently being investigated. In this review, we summarize reports relating to clemastine administration for white matter injury and neurological disease and discuss the therapeutic potential of remyelination promotion.